2022
DOI: 10.1007/s10943-022-01616-3
|View full text |Cite
|
Sign up to set email alerts
|

Australian Patient Preferences for the Introduction of Spirituality into their Healthcare Journey: A Mixed Methods Study

Abstract: While patients value engagement concerning their spirituality as a part of holistic healthcare, there is little evidence regarding the preferred way to engage in discussions about spirituality. This study investigated inpatient preferences regarding how they would like spirituality to be raised in the hospital setting. A cross-sectional survey was conducted with inpatients at six hospitals in Sydney, Australia (n = 897), with a subset invited to participate in qualitative interviews (n = 41). There was high ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…In one study, only 10% of a sample of internal medicine clinic patients would discuss spiritual issues in lieu of discussing medical problems with their doctors (MacLean et al, 2003 ). This was reflected in the attitude expressed by this cohort that spiritual issues are less likely to be present if illness is not severe (Best et al, 2022a , 2022b ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In one study, only 10% of a sample of internal medicine clinic patients would discuss spiritual issues in lieu of discussing medical problems with their doctors (MacLean et al, 2003 ). This was reflected in the attitude expressed by this cohort that spiritual issues are less likely to be present if illness is not severe (Best et al, 2022a , 2022b ).…”
Section: Discussionmentioning
confidence: 94%
“…A previous paper from this study reported Australian patient preferences as to how they would like to be asked about their spirituality. It found that there was high patient acceptance for discussing spiritual issues in healthcare, but that relevance depended on context (Best et al, 2022a , 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…An empirically based training program was developed by the authors. Four studies were conducted to establish the content and format of the training (Best et al, 2022a ; Jones et al, 2021a , 2021b , 2022c ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of spiritual care with Australian healthcare professionals have revealed that perspectives on spirituality and spiritual care may differ substantially from countries where Christianity plays a culturally more significant role, such as the USA (Best et al, 2022a ; Jones et al, 2021b ). The latest census data reveal that more Australians are reporting “no religion” (38.9% in 2021, compared with 30.1% in 2016) and that those who identify as Christian are declining (43.9% in 2021 compared to 52.1% in 2016) (Australian Bureau of Statistics, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in spirituality and spiritual care has increased in recent years, and a growing amount of literature reveals that it is seen in the nursing profession as important to patient health and healing (Hvidt et al, 2020;Weathers et al, 2016) but that it is still not well understood or frequently practiced (Chen et al, 2020;McSherry, 2020). While there has been a significant amount of spiritual care research in palliative care nursing (Nolan et al, 2011;Tan Jr., 2019) and in the chaplaincy literature (Poncin et al, 2019), limited research has been identified addressing spiritual issues in the acute care setting (Cone & Giske, 2017;Giske & Cone, 2015), nursing homes (Dewittea et al, 2021;Gordon et al, 2020), mental health (Holmberg et al, 2021;Patterson et al, 2018), paediatrics (Fazlollahi et al, 2022) or from the patient perspective (Best et al, 2022;Cone & Giske, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%